1991
DOI: 10.1136/sti.67.2.92
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with clinical and sub-clinical anal human papillomavirus infection in homosexual men.

Abstract: IntroductionThe increase in the number of reports of anal intraepithelial neoplasia (AIN), carcinoma-in-situ and squamous cell carcinoma in association with anal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

1991
1991
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
10
0
4
Order By: Relevance
“…In a recent study which we carried out on anal HPV infection in a group of homosexual men, no relationship was detected between the practice of receptive anal intercourse and either clinical or sub-clinical anal HPV infection. 6 However, the validity of this observation required further investigation because those who admitted to receptive anal intercourse were over-represented (104 of the 112 subjects, 93%). We therefore decided to study anal HPV infection in a different group ofpatients, where it was suspected that the practice of receptive anal intercourse would not be as prevalent.…”
Section: Introductionmentioning
confidence: 95%
“…In a recent study which we carried out on anal HPV infection in a group of homosexual men, no relationship was detected between the practice of receptive anal intercourse and either clinical or sub-clinical anal HPV infection. 6 However, the validity of this observation required further investigation because those who admitted to receptive anal intercourse were over-represented (104 of the 112 subjects, 93%). We therefore decided to study anal HPV infection in a different group ofpatients, where it was suspected that the practice of receptive anal intercourse would not be as prevalent.…”
Section: Introductionmentioning
confidence: 95%
“…Studies comparing groups of women by HIV status using PCR-based methods have reported an HPV prevalence range of 40 to 77.4 percent for HIV-positive women and 14 to 62 percent for HIV-negative women (Ahdieh et al, 2001, Critchlow and Koutsky, 1995, Ellerbrock et al, 2000, Hankins et al, 1999, Langley et al, 1996, Maiman et al, 1998, Massad et al, 1999, Minkoff et al, 1998, Moscicki et al, 2000, Palefsky et al, 1999, Rezza et al, 1997, Shah et al, 1997, Silverberg et al, 2002, Sun et al, 1995, Sun et al, 1997, Temmerman et al, 1999, Wright et al, 1994a. A similar increase in prevalence has been observed in populations of HIV -positive men (Breese et al, 1995, Kiviat et al, 1993, Law et al, 1991, Palefsky et al, 1994. Renal allograft recipients also appear to be at an increased risk of HPV infection, with recipients demonstrating consistently higher prevalence of HPV 16 or 18 DNA than controls (Alloub et al, 1989, Fairley et al, 1994a, Ogunbiyi et al, 1994.…”
Section: Prevalence In Immunosuppressed Individualsmentioning
confidence: 58%
“…HPV DNA (types 6/11, 16/18) by dot bIot hybridization was detected in 40% (6/11 in 18%; 16/18 In 11%; both groups In dyspIasia, but not between HPV infection or anal dysplasia and HIV-positivity, immune status, sexual practices or other sexuaIly transmitted diseases (Law et al, 1991). ln a larger study (Kiviat et al, 1993), a random sample of 285 HIV-positive and 204 HIV-negative homosexuaI men was surveyed.…”
Section: Anorectal Intraepithelial Neoplasia and Invasive Cancermentioning
confidence: 95%